Semiotic technology as material resonance of postcolonial aesthetics in digital children’s picture book apps - P.Dhayapari Perumal; Shanthini Pillai Joseph Sandra; Melissa Shamini Perry (Penerbit Universiti Kebangsaan Malaysia, 2021)
Children’s literatures presently are produced widely through media production either as remediation of printed stories or originally produced in digital form. The current most sought after digitized communicative practice of the media is the digital children’s picture book app due to its multimediality and interactivity. This quality of the picture book app paves the path for an aesthetic and cultural transformative exchange. However, these digital children’s picture book apps have been found to contain diversity and multicultural gaps. Furthermore, the noncognitive/ affective quality of these interactive digital book apps that is evoked through senses like touch, hearing and sight needs further investigation. Hence, through a qualitative approach, the digital children’s picture book app version of the Malaysian animated series Upin and Ipin: Storybook: The Rain and The Sea Part 1 was selected as case study for this paper. Selection criteria consisted of three aspects; narration being in English and contained Semiotic Technology i.e. digitized meaning-making modes, the contents reflect characters, symbols and narratives that portray Malaysian culture, history and identity. The research reveals a postcolonial aesthetic that extensively operates based on the ideologies of the dominant class or culture through the representations of ethnic nationalism. This shows a builtin intrinsic value according to the context of the dominant culture that can be found in the aesthetic engagement in the transcultural space of this picture book app. This article contributes to scholarship cross-cultural engagement in the affective space of postcolonial digital picture books.